Dignità dello straniero. Da Sharmin a Walid: due immagini dell’immigrato in Italia a confronto - Puto, Małgorzata (Romanica Silesiana)
The analyzed texts are definitely challenging borders and limits, including those of immigration, that means the exploration of the marginalized aspects of life and marginalized elements of society. They put a great emphasis on the human as physical beings in a physical world, the human that try to live their lives in the meaningful and conscious way. They struggle against a world in which they are emarginated. The stories of the immigrants could be seen as the reconceptualization of the Italian society, its history that in this case refers to postcolonial consequences and the cultural constructs. The immigrants in Italy should no longer look for a pattern of life, they’d rather celebrate its specificity and try to be moral creatures, replacing stereotypes with their genuine experiences. Key words: Challenging borders, limits, immigration, conscious life.